CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM PEMBELAJARAN PAI DI SDN 02 PERCONTOHAN - Riski Pratama, Andy (STAI Darul Kamal Darul Kamal NW Kembang Kerang, 2023)
This research discusses the effectiveness of implementing Contextual Teaching and Learning (CTL) in Islamic Religious Education (PAI) learning at SDN 02 Pilot. This research uses a qualitative descriptive approach with a phenomenological approach, which aims to understand the reality of events and various activities that occur in the learning process using a contextual approach at the school. The data sources for this research were SDN 02 Perpilotan students and PAI teachers, and data was collected through observation, interviews and documentation. Research data was analyzed descriptively qualitatively, starting with coding, transcription and reduction. The results of data analysis reveal that the application of PAI learning with a contextual approach at SDN 02 Pilot is in accordance with the main components of the contextual approach, such as constructivism, discovery, questioning, learning communities, modeling, reflection and authentic assessment. Apart from that, PAI learning with a contextual approach is also effective in supporting students' academic achievements and their understanding of the application of learning in everyday life. This learning becomes meaningful, cheerful and enjoyable (joyful learning) for students.